Tobacco smoking and COVID-19 pandemic: old and new issues. A summary of the evidence from the scientific literature - Cattaruzza, Maria Sofia; Zagà, Vincenzo; Gallus, Silvano; D'Argenio, Paolo; Gorini, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
Introduction: COVID-19 pandemic burst onto the international scene as a new disease not affecting patients uniformly; hence it has risen many questions yet to be clarified. The aim of this study was to outline the main issues that led tobacco smoking being discussed as a potential risk factor associated with COVID-19. Methods: articles from MEDLINE and pre-prints published from January to April 2020 were identified. Results: data from China showed that men had more severe outcomes of COVID-19 than women. Since smoking prevalence is very high among Chinese men in comparison to women, it was hypothesized that smoking could be a risk factor for poor prognosis. This was also supported by the higher prevalence of comorbidities, many of which are tobacco-related diseases, in patients with severe COVID-19, who were also more likely to have a smoking history. A meta-analysis confirmed these results reporting an OR=2.25 (95% CI: 1.49-3.39) for developing severe Covid-19 among patients with a smoking history. Some authors, noticing that reported smoking prevalence among hospitalized patients was substantially below smoking prevalence in the corresponding populations, speculated a protective role of nicotine. However, it is likely that low prevalence among hospitalized patients are partially due to many smokers misclassified as nonsmokers. Tobacco smoking seems to cause a dose-dependent upregulation of the angiotensin-converting- enzyme-2 (ACE2), the virus cellular entry receptor, which could explain the higher risk of severe COVID-19 in smokers. Conclusions: There is need for further independent studies to clarify the role of smoking on COVID-19 incidence, progression and mortality.